Financial Reporting and Tax Calculator Application “AccounTax”: Is It Feasible to Develop for MSMEs in Indonesia? - Rachmawati, Nurul Aisyah; Ramayanti, Rizka; Setiawan, Rudi (Jati: Jurnal Akuntansi Terapan Indonesia, 2025)
Preparing financial and tax reports is challenging for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. It occurs because of a lot of the obstacles they face, like limitations in knowledge, time, and human resources. This study developed a financial reporting and tax calculator application that can be used as one solution for resolving problems faced by MSME actors. So, it is necessary to conduct a feasibility test on the development of this application. The TELOS (Technical, Economic, Legal, Operational, Schedule) approach was applied in this feasibility study with a descriptive qualitative approach. The results show that the financial reporting and tax calculator application “AccounTax” is feasible for development in terms of technical, economic, legal, operational, and schedule. This application can, therefore, be distributed to MSMEs to help with the process of creating financial and tax reports for MSMEs.